A dependência de internet e suas principais alterações nas ocupações de estudantes: uma revisão sistemática - SOUSA, Leonardo Lucas de (2023)
Attention must be paid to the negative use of the Internet, which can cause damages in the various spheres of society if the use of the Internet improperly occurs. From the perspective that the engagement of the individual may be occurring centrally only i n one activity to the detriment of others, it is necessary to develop research that focuses on analyzing the influences of the internet on the occupational performance of people. Occupational Therapy observes and analyzes performance skills in order to understand the transaction among the basic factors that support or not the involvement in occupation and occupational performance. Thus, we seek to analyze in the scientific literature, through a systematic review, the main repercussions that Internet depende nce (DI) can cause on the students' occupational performance and to develop theoretical discussion on the subject as a result of ID. In order to do so, we used criteria established in the PRISMA recommendation for the elaboration of this review, using as t erms / descriptors the following: internet addiction / internet addiction; occupations / occupation and students / students. In Portuguese and English, cited in the title or subject. The period of search of publications was between November and December 2017, through the electronic databases PubMed, International Literature in Health and Biomedical Sciences (Medline) and Scientific Electronic Library Online (Scielo). During the search a total of 2,189 publications were identified, of which 2,168 were excluded during the title analysis, leaving 21 publications. The application of the adapted test of Azevedo (2010) allowed the exclusion of 08 papers, since they did not reach the established insertion criteria. Therefore, the final sample consisted of 13 studies. These were analyzed and their data extracted according to the extraction route. From the extraction of the characteristics of each study, inferences were made about the main occupations presented in these as regards the influences of DI on the occupatio nal performance of individuals in their activities. The occupations of social participation, education, rest and sleep and work appear 19 times in the articles analyzed. In addition, there were nine citations about impairments in social participation (47% of the final sample), six showed deficits in education (33%), two in work activities (10%) and two in rest and sleep engagement (10%). . It leaves as a conclusion the indicative for more indepth research on this subject.